2007
DOI: 10.1242/jcs.005124
|View full text |Cite
|
Sign up to set email alerts
|

Chitin synthase III requires Chs4p-dependent translocation of Chs3p into the plasma membrane

Abstract: In Saccharomyces cerevisiae, Chs4p is required for chitin synthase III (CSIII) activity and hence for chitin synthesis. This protein is transported in vesicles in a polarized fashion independently of the other Chs proteins. Its association with membranes depends not only on prenylation, but also on its interaction with other proteins, mainly Chs3p, which is the catalytic subunit of CSIII and is able to properly direct Chs4p to the bud neck in the absence of prenylation. Chs4p is present in functionally limitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
90
0
10

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(109 citation statements)
references
References 40 publications
9
90
0
10
Order By: Relevance
“…Interestingly, these fks1 ts mutants also showed defects in endocytosis. It was previously reported that blockade of endocytosis stops internalization of Chs3p, the chitin synthase subunit, leading to a significant increase in chitin synthesis (Reyes et al 2007). Therefore it is possible that loss of Fks1p function induces chitin accumulation due to defective endocytosis, to repair cell wall damage caused by 1,3-b-glucan shortage.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, these fks1 ts mutants also showed defects in endocytosis. It was previously reported that blockade of endocytosis stops internalization of Chs3p, the chitin synthase subunit, leading to a significant increase in chitin synthesis (Reyes et al 2007). Therefore it is possible that loss of Fks1p function induces chitin accumulation due to defective endocytosis, to repair cell wall damage caused by 1,3-b-glucan shortage.…”
Section: Discussionmentioning
confidence: 99%
“…This interaction mediates the anchorage of Chs4 to septins through Bni4 (16,26). In addition, Chs4 promotes CSIII activation (37).…”
mentioning
confidence: 98%
“…However, Chs3 and Chs4 do not colocalize during all phases of the yeast cell cycle. Moreover, they engage in different routes of trafficking to the plasma membrane (Grabinska et al , 2007 ;Reyes et al , 2007 ;Meissner et al , 2010 ). Chs4 connects the CSIII activity to the septin ring by interacting with the scaffold protein Bni4, which in turn binds to Cdc10 (one of five septins) (DeMarini et al , 1997 ).…”
Section: Early Compartmentation At the Incipient Bud Sitementioning
confidence: 99%
“…Anchoring to the septins involves Chs4, Bni1, and Glc7 Chuang and Schekman , 1996 ;Ziman et al , 1996 ;Kozubowski et al , 2003 ;Roncero and Sanchez , 2010 Chs4 Localization is similar but not identical to that of Chs3 Regulatory subunit of the CSIII complex, tethers to the septin ring by binding to Bni4. Chs4 is transported to the plasma membrane independently from Chs3 trafficking Trilla et al , 1997 ;Grabinska et al , 2007 ;Reyes et al , 2007 ;Meissner et al , 2010 Bni4 Single ring at most nonbudded and small/ medium-budded cells; double ring in most large-budded cells Regulatory subunit of Glc7, binds to the Cdc10 septin and to…”
Section: Referencementioning
confidence: 99%